Effect of inclined rowing machine on FES-assisted indoor rowing exercise performance - Hussain, Zakaria; Tokhi, M. O.; Jailani, Rozita; Ahmad, Salmiah; Ibrahim, Babul Salam K.K. (2009)
This paper describes the effect of inclined track in an indoor rowing machine on the rowing exercise for paraplegics. The indoor rowing exercise is introduced as a total body exercise for rehabilitation of function of lower extremities through the application of functional electrical stimulation (FES). A model of the machine is developed using the Visual Nastran (Vn4D) software environment. Nine different degrees of inclination are set. Fuzzy logic control is implemented to control the knee and elbow trajectories for each of the inclination angle. The generated level of electrical stimulations for activation of quadriceps and hamstrings muscles are recorded and analysed. The results show that the highest efficiency is achieved at 7° of inclination. In view of good results obtained, it is concluded that different angles of track inclination significantly affect the level of electrical stimulation required to assist paraplegics’ indoor rowing exercise.